Tax Interaction Among Walloon Municipalities: Is There Room For Partisan Monopoly Effect? - Laurent Van Malderen; Marcel Gérard (European Regional Science Association (ERSA), 2012)
Three sources of tax interactions among local jurisdictions are usually considered in the literature: public expenditure spill-over, tax competition and yardstick competition. However, another source of interdependency has been suggested in recent years: the `political trend'. According to this hypothesis, politicians of the same party tend to behave in the same way as a partisan reference group (Santolini, 2008). In fact, citizens also vote based on ideology. Political parties provide important cues on how politicians will act when elected. As a result, local incumbents of the same party are more likely to mimic each other's policies and to adopt similar policies. Moreover partisan politics may also act through the presence of a monopoly power effect linked to several terms of power for the same party consecutively. The aim of this paper is to propose an empirical analysis of tax interactions among the municipalities (i.e. the local jurisdictions) of the Walloon Region (southern part of Belgium) and to discriminate among the difference sources of interactions. The `political trend' hypothesis is tested, as well as a potential partisan monopoly power effect. According to this hypothesis, a political party is more likely to have implemented tax rates corresponding to its ideology if it has ruled the municipality several legislatures in a row. To conduct that research spatial econometrics tools are used along a panel of Walloon local tax rates data from 1983 to 2008 and political data. The results obtained so far first show that yardstick competition exists among Walloon municipalities. Second, the `political trend' hypothesis is rejected by our data; this means that local incumbents do not follow some party discipline rule in tax matters at the local level. But, and importantly, we find out that a partisan monopoly power effect is at work in Walloon municipalities: several terms of a left-wing party increase the tax rates. Finally presence of an electoral cycle is also clearly documented.
Keywords: 330